Length-Weight Relationship and Condition Factor of Spiny Gurnard (Lepidotrigla dieuzeidei Blanc and Hureau, 1973) Inhabiting Northeast Mediterranean Sea - Basusta, Asiye; Basusta, Nun I.; Calta, Metin; Ozer, Ebru I.; Girgin, Huya (Medwell Online, 2013)
The aim of this study was to determine length-weight relationships and to give the maximum length spiny gurnard (Lepidotrigla dieuzeidei Blanc and Hureau, 1 973) inhabiting Northeast Mediterranean Sea. A total of 1910 spiny gurnard, (Lepidotrigla dieuzeidei Blanc Hureau, 1 973) were obtained from the fishermen on September 2012 to October 201 2 in the Northeast Mediterranean Sea. Total length of samples ranged between 7.2-20.4 cm (female), 7.1-17.9 cm (male) and weight 2.28-63.08 g (female), 1.90-47.12 g (male) for L. dieuzeidei, respectively. The length-weight relationships of L. dieuzeidei were found as W = 0.0034 TL3.35 (R-2 = 0.83) for all specimens, W = 0.003TL(3.41) (R-2 = 0.84) for females and W = 0.004TL(3.28) (R-2 = 0.81) for male, respectively. The types of growth for both sexes were positive allometric growth for spiny gurnard. The condition factor values varied between 0.8017 +/- 0.0057 (female), 0.8076 +/- 0.0061 (male) in L. dieuzeidei b-value has been identified as 3.3052, 3.2176, 3.2664, male, female and for all individuals in L. dieuzeidei, respectively. The difference of length-weight relationship between L. dieuzeidei was statistically insignificant (p>0.05). This study presented the first reference on LWRs and condition factor for spiny gurnard from NE Mediterranean coast of Turkey.
Keywords: Lepidotrigla dieuzeidei; spiny gurnard; Northeast Mediterranean; length-weight relationship; condition factor